Analysis of the Effectiveness and Contribution of Hotel Tax and Restaurant Tax to Regional Original Revenue in Sleman Regency - Al Amaru, Bukhori Hiro Fajar; Putry, Nur Anita Chandra; Ayem, Sri (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The purpose of this research is to ascertain how much of an impact the hotel and restaurant taxes have on Sleman Regency's Regional Original Revenue (PAD).  Secondary data was collected from Sleman Regency's Budget Realization Reports for 2019–2023.  Descriptive quantitative analysis is the methodology used in this study.  From 2019 to 2023, the hotel tax in Sleman Regency was 108.82% effective and the restaurant tax was 110.35% effective, putting them in the extremely effective category, according to the data.  The average hotel tax contribution to Regional Original Revenue is 10.55%, which is considered very low, while the average restaurant tax contribution is 11.59%, which is also considered poor.  This bodes well for the future of the hotel and restaurant industries in Sleman Regency, which might be a major driver of Regional Original Revenue growth.